Are Myxobacteria intelligent? - Kaiser, Armin D. (Frontiers in Microbiology, 2013)
“Intelligence” is understood in different ways. Because humans are proud of their ability to speak, intelligence often includes the ability to communicate with others, to plan for the future, and to solve frequently encountered problems. Myxobacteria are among the most socially adept and ubiquitous of bacteria that live in the soil. To survive in nature, Myxobacteria communicate with their peers, using signals that elicit specific responses. Both swarming-growth and starvation-induced fruiting body development depend upon the specificity and effectiveness of signals passed between cells. Dynamic swarms spread outward, forming regular multi-cellular and multi-layered structures as they spread. Several different extra-cellular signals have been identified for fruiting body development and one is hypothesized for swarm development. Some extra-cellular signals are small, diffusible molecules. Others are protein molecules. The swarm signal appears to consist of structurally complex, protein to protein, contact junctions between pairs of side by side aligned cells. Each junction persists for less than a minute before disconnecting. After separating, both cells move on to make similar, transient connections with other cells. Eventually, the signal spreads across a prescribed population of communicating cells.